Words of life in japanese culture (2020)
There are words within the Japanese culture that encompass concepts as deep as the meaning of life: Ikigai. Likewise, other concepts, such as meraki or nankurunaisa, relate respectively to a creative and passionate way of performing actions, and with hope for a promising future. These concepts arise from the roots of culture, history, and context.